Ce4+ as a facile and versatile surface modification reagent for templated synthesis in electrical applications. Issue 5 (21st January 2019) - Yao, Lulu; Gu, Jiajun; Wang, Weiqiang; Li, Tengfei; Ma, Dongling; Liu, Qinglei; Zhang, Wang; Abbas, Waseem; Bahadoran, Ashkan; Zhang, Di
Abstract : Ce 4+ is a facile and versatile surface modification reagent for various substrates, producing versatile platforms for fabricating 3D architectured materials. Abstract : Surface modification for templated synthesis is crucial to achieving three-dimensional (3D) architectured materials for catalysis, photonics, energy storage, etc . However, the existing facile and versatile modification methods ( e.g. with dopamine and catechol) generate modification layers that are unstable in harsh environments. These methods are thus unsuitable for electrical applications. Here we report that Ce 4+ can act as an effective surface modification reagent for a broad range of substrates (chitinous butterfly wings, carbon paper, nickel foam, and polyethylene terephthalate planks) with various structural features owing to its strong oxidizing ability and Lewis acid nature. The modification yields discrete CeO2 seed layers on substrate surfaces in ca. 0.25–2 h, important for the subsequent conformal growth of CeO2 nanoparticles, Ni(OH)2 nanowires, FeOOH nanosheets, and WO3 nanosheets into 3D architectured materials. The conformally synthesized FeOOH on nickel foam (NF) yields an overpotential of 241 mV at 10 mA cm −1 for an oxygen evolution reaction. This value is comparable to a typical catalyst Ni(Fe)OOH-NF for which the Ni/Fe ratio must be well-optimized. This facile and versatile strategy might have broad applications in the conformal fabrication and application of 3D architectured materials, especially when applied in electrical applications of architectured materials ( e.g. Li-ion battery).